CHEMICAL AND MICROSTRUCTURAL CHANGES IN EUCALYPTUS GLOBULUS FIBERS SUBJECTED TO FOUR DIFFERENT PRETREATMENTS AND THEIR INFLUENCE ON THE ENZYMATIC HYDROLYSIS - Troncoso, Eduardo; Castillo, Rosario; Valenzuela, Roberto; Reyes, Pablo; Freer, Juanita; Norambuena, Marcela; Rodríguez, Jaime; Parra, Carolina (Journal of the Chilean Chemical Society, 2017)
In order to understand the relation between chemical composition, microscopic structure and enzymatic digestibility, different Eucalyptus globulus Wood pretreated samples were examined. Pretreated materials obtained by steam explosion and autohydrolysis were compared with those obtained by organosolv and kraft processes. Chemical analyses of pretreated materials showed a decrease in the content of xylans, except in the kraft pulp. FT-IR spectra showed that the residual lignin in autohydrolysis pulp had experienced greater changes compared to those in steam explosion and organosolv pulps, whereas minor changes in lignin kraft pulp were observed. The fiber morphology indicated that autohydrolysis pretreatment was the most aggressive treatment. Reduction in the content of lignin and its redistribution on the fiber wall were confirmed through confocal laser microscopy. The formation of discrete lignin droplets deposited on the surface of the fibers was observed in all pretreatments, with a higher frequency in organosolv followed by steam explosion. A significant increase in enzymatic accessibility was achieved in organosolv, autohydrolysis and steam explosion pulps, due to xylans removal combined with lignin redistribution. Homogeneous lignin distribution and higher xylan content may be related to the low enzymatic hydrolysis efficiency in kraft pulp.